National Conference: Why attend a conference? Insights from the ORNAC 2025 Conference Lead - Hahn, Bryana (Operating Room Nurses Association of Canada Journal, 2025)
If you’ve recently attended an in-person conference, you likely already know the value it brings. For those who haven’t had the opportunity yet, or if it’s been a while since your last experience, let me share what I believe are some of the most important takeaways from attending in-person conferences.